A Pilot Study on Part-Time Occupational Therapy Students’ Engagement and Academic Performance in Learning Neuroanatomy using Canvas LMS - Mohd Din , Aisha; Ismadi , Nur Amira; Ali Hussain Alashkham , Fatma; Abdul Latiff , Amir Muhriz (Environment-Behaviour Proceedings Journal, 2025)
Neuroanatomy is a challenging subject for part-time occupational therapy students. The use of Learning Management Systems (LMS) can provide flexible platforms that provide interactive e-resources to increase student engagement in neuroanatomy. This pilot study aimed to determine the students’ engagement level on Canvas LMS and correlate with their academic performance. The Student Engagement Questionnaire was used to assess engagement levels, and final exam grades were analysed. Results showed that 63% of students demonstrated good engagement, with a noticeable improvement in academic performance. In conclusion, Canvas LMS effectively supports engagement and enhances academic outcomes in neuroanatomy for part-time occupational therapy students.